Wyndham Lewis's literary work 1908-1928 : vorticism, futurism and the poetics of the avant-garde - Macedo, Ana Gabriela (2014)
The focus of this thesis is Wyndham Lewis’s early literary work, namely: The Wild Body, an anthology of stories mainly written in the pre-war years and revised in 1927, Tarr, a semi-autobiographical Vorticist novel first published in 1918, and Enemy of the Stars, a Vorticist play first published in the magazine Blast in 1914. These texts are studied in the context of the Vorticist movement, of which Lewis was a leader and main entrepreneur and also in connection with the principles and manifestos of the Futurist movement. The methodology used draws on the work of Julia Kristeva on the poetics of the avant-garde for the analysis of the vorticist/futurist “revolution in language”, and Mikhail Bakhtin’s theory of the “carnivalesque literary genre”. Thus, the texts by Lewis referred to above will be analysed in the light of the concepts of popular and modernist grotesque, carnivalesgue and polyphony. The poetics and politics of Wyndham Lewis’s vorticist discourse are here analysed and understood as aesthetics of challenge and provocation, transgressive in its incorporation of society’s own fragmentation and ideological crisis, rather than as an aesthetics of compensation within the context of Modernity.